The Development of Foodivity Interactive as an Interactive Multimedia to Improve Students’ Understanding of Food Nutrition Topic - Sulistinayah Suwaka Putri; Ari Widodo; Yaya Wihardi (Journal of Science Learning, 2022)
The pandemic of COVID-19 has affected the education sector. All school access is restricted, transforming education into distance learning. This encourages educators to explore alternative methods for improving students' understanding. Interactive multimedia is a method of learning media that can promote efficiency, motivation, and student understanding of subjects. This research aims to measure the students' understanding of nutrition by developing festivity interactive as interactive multimedia. A pre-experimental one-group pretest-post-test design was adopted. Developing multimedia using the instructional design process ADDIE (Analysis, Design, Develop, Implement, and Evaluate). The research subject was 53 junior high school students in West Java, more precisely in two locations, Sukabumi and Kuningan. The instrument consisted of an expert judgment rubric, a student questionnaire, and a multiple-choice objective test with pretest and post-test. The V Aiken index shows an average validation of 0.8125, indicating that the media is valid and can be used. Students responded positively to the questionnaire by a percentage of 93.01 percent. Based on the analysis, the N-gain value on students' understanding is 0.35. This indicates increased students’ expert judgments in the moderate improvement category between the pre-and post-tests. The hypothesis test establishes that hypothesis H1 is acceptable, showing a significant difference between pre-and post-tests. These results indicate that using Foodivity Interactive as an Interactive Multimedia can enable students’ understanding of nutrition topics.